A Mechanistic, Stochastic Model Helps Understand Multiple Sclerosis Course and Pathogenesis. (12th March 2013) - Bordi, Isabella; Umeton, Renato; Ricigliano, Vito A. G.; Annibali, Viviana; Mechelli, Rosella; Ristori, Giovanni; Grassi, Francesca; Salvetti, Marco; Sutera, Alfonso
Abstract : Heritable and nonheritable factors play a role in multiple sclerosis, but their effect size appears too small, explaining relatively little about disease etiology. Assuming that the factors that trigger the onset of the disease are, to some extent, also those that generate its remissions and relapses, we attempted to model the erratic behaviour of the disease course as observed on a dataset containing the time series of relapses and remissions of 70 patients free of disease-modifying therapies. We show that relapses and remissions follow exponential decaying distributions, excluding periodic recurrences and confirming that relapses manifest randomly in time. It is found that a mechanistic model with a random forcing describes in a satisfactory manner the occurrence of relapses and remissions, and the differences in the length of time spent in each one of the two states. This model may describe how interactions between "soft" etiologic factors occasionally reach the disease threshold thanks to comparably small external random perturbations. The model offers a new context to rethink key problems such as "missing heritability" and "hidden environmental structure" in the etiology of complex traits.